EFEKTIFITAS KONSENTRASI NIRA LONTAR DALAM ASAP CAIR TEMPURUNG KELAPA TERHADAP KADAR PROKSIMAT CAKALANG (Katsuwonus pelamis L.) ASAP - Naema Bora; Ludia S Gasong (Politeknik Pertanian Negeri Kupang, 2021)
This study aims to determine the effect of differences in the concentration of palm sap in coconut shell liquid smoke on proximate levels of skipjack flavor smoke. The study used an experimental method with four single treatments, namely the concentration of palm sap and liquid smoke from coconut shells. The parameters measured were proximate levels, which included: water content (%), texture, protein content and total colonies microbial. The results showed that: (1) The use of palm oil in liquid smoke of coconut shell significantly improved the quality of skipjack smoked during the storage period; (2) The concentration of lontar sap in liquid smoke has a significant effect on the organoleptic quality of skipjack during the storage period; (3) The concentration of palm sap of 25%+75% of coconut shell liquid smoke significantly improves the quality of the skipjack smoked which includes moisture content, texture, pH and protein content. Key Words: Concentration of palm sap, liquid smoke, quality skipjack tuna